Benefits and risks of ureteral access sheaths for retrograde renal access. Issue 1 (January 2016) - Breda, Alberto; Territo, Angelo; López-Martínez, Juan Manuel
Abstract : Purpose of review: Ureteral access sheath (UAS) became increasingly popular worldwide. However, the safety of its routine use remains controversial. The aim of the current revision is to provide a systematic review on the benefits and disadvantages of the UAS. Recent findings: A systematic review was performed following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses criteria. Two reviewers independently searched the literature, finally identifying 20 articles valuable for this review. The use of UAS demonstrated several advantages to facilitate retrograde intrarenal access, lower intrarenal pressure, protect the ureter, protect the scope, and expedite stone extraction. Despite this, there is also some evidence that UAS use may be associated with acute ureteral injury and long-term complications, apparently related to maneuvers for UAS insertion and mucosal or deeper layers of injury and ischemia. Furthermore, there are still pending questions on the possible increase in stone-free rates, and decrease in operative time and costs. Summary: Although the use of UAS is associated with some risk and limiting factors, it appears from this systematic review that its use is common and safe for the retrograde intrarenal access. Therefore, UAS is highly recommended for the treatment of upper tract disease by means of retrograde intrarenal surgery.